1970
DOI: 10.1128/jb.102.3.877-878.1970
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids from Vegetative Cells and Spores of Bacillus stearothermophilus

Abstract: In spores of Bacillus stearothermophilus produced at 45 and 55 C, branched-chain fatty acids predominated in the former and straight-chain acids in the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…A decrease in the total amount of branched fatty acids with increasing growth temperature has been reported in several investigations of Bacillus species (4,8,44,47,52,56). This trend was most obvious in B. stearothermophilus (8,47,56) and was, in this species, accompanied by a drastic increase in the amount of n-C16. In strain Ot 32 grown between 50 and 70°C and in strain Ft R32, the total amounts of branched fatty acids decreased 8 and 15% (mol/mol), respectively, with concomitant increases in the amounts of n-C16 and n-C18.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A decrease in the total amount of branched fatty acids with increasing growth temperature has been reported in several investigations of Bacillus species (4,8,44,47,52,56). This trend was most obvious in B. stearothermophilus (8,47,56) and was, in this species, accompanied by a drastic increase in the amount of n-C16. In strain Ot 32 grown between 50 and 70°C and in strain Ft R32, the total amounts of branched fatty acids decreased 8 and 15% (mol/mol), respectively, with concomitant increases in the amounts of n-C16 and n-C18.…”
Section: Discussionmentioning
confidence: 74%
“…The synthesis of unsaturated acids by the genus Bacillus has been reported for B. stearothermophilus (8,15,56) and for a number of mesophilic and psychrophilic species (15,21,22 with n-Cl6 and iso-C16 replaced iso-C15 at 40°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the significance Of the difference in the fatty acid composition between vegetative cells and spores is unknown, one possibility is that it provides a unique method of increasing the rigidity of spore membrane lipids by decreasing the low melting point (23 C) a-C15 fatty acid and increasing the high melting point (54 C) n-C14 fatty acid (28). Studies on other Bacilli (29)(30)(31) have also reported variations in the fatty acid composition between spores and vegetative cells, but the direction of this change has not been consistently towards increasing the high melting point fatty acids in membrane lipids.…”
Section: Fatty Acid Composition Of Vegetative Cells and Spores Grown mentioning
confidence: 99%
“…The class of fatty acid present in greatest quantity in thermophilic bacteria is iso-branched (1,20,26). In the gram-positive organisms examined, lowering the incubation temperature for growth generally results in an increased proportion of unsaturated fatty acids, whereas a lowering of the incubation temperature for gramnegative thermophilic bacteria results in a larger proportion of small, branched-chain fatty acid in the cells (12,23,28).…”
mentioning
confidence: 99%